Towards a physical description of habitat: quantifying environmental adversity (abiotic stress) in temperate forest and woodland ecosystems - Ladd, Brenton; Bonser, Stephen P.; Peri, Pablo Luis; Larsen, Joshua R.; Laffan, Shawn W.; Pepper, David A.; Cendón, Dioni I. (Wiley, 2025)
1. Our aim was to develop a quantitative proxy for environmental adversity (abiotic stress) in temperate Eucalyptus and Nothofagus forest and woodland ecosystems. 2. Samples and measurements were collected at 42 sites across a rainfall gradient in southern Australia, an elevation gradient in south-eastern Australia, and a longitudinal transect (temperature gradient) in Patagonia, Argentina. 3. We compared the ability of (a) abiotic variables (14 soil and 21 climatic variables) and (b) the stable carbon isotope (d13C) values of soil organic matter (SOM), to predict variation in leaf area index (LAI; a forest productivity variable). 4. The d13C of SOM (soil aggregates) explained more variation (57%) in LAI than multivariate statistical models that integrated information on many abiotic variables. W* (a climatic water balance model) was also a powerful predictor variable, explaining 37% of the variability in LAI. 5 Synthesis. The stable carbon isotopic signature of soil aggregates is a powerful explanatory variable that may help us to quantify environmental adversity (abiotic stress) in temperate forest and woodland ecosystems.